THE EFFECT OF ELECTRONIC WORD-OF-MOUTH IN SOCIAL MEDIA TOWARD CONSUMER PURCHASE DECISION WITH BRAND IMAGE AS MODERATING VARIABLE - PRAMESTIARA, ANINDYA; RAHAB, RAHAB (JOURNAL OF RESEARCH IN MANAGEMENT, 2018)
Social media has made it possible for users to exchange information and discuss theiropinions and experiences about products or services through online on their social mediaplatform with their peers. This kind of communication is called as electronic word-of-mouth(e-WOM) where the information can be spread faster and has the potential for greaterimpact on consumers purchase decision. Therefore, the aim of this research is to know theeffect of e-WOM (including quality and quantity of e-WOM as well as sender?s expertise) insocial media on consumers? purchase decisions moderated by brand image. The researchmethodology used for this study is a case study with survey research method. Conveniencesampling technique derived from non-probability sampling techniques are used for sampleselection. The sample of this research is 175, from people who have purchased and usedEtude House product. Statistical software SPSS and AMOS is used to analyze the data. Thefindings in this area will help Etude House and other marketers to reach out its potentialcustomers and align their marketing effort in efficient way by pay attention on the marketingpolicies about eWOM. The limitations of the research is some respondents not read andanswer the question clearly and made it not represent their exact perception.